PENGEMBANGAN WEBSITE PENGELOLAAN PRAKTIKUM PADA PROGRAM STUDI BIOLOGI FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN ALAM UNIVERSITAS PALANGKA RAYA - Widiatry Widiatry; Nadia Olivia Anggraini (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2021)
Learning at this time not only through materials but also by practicing. With the current manual system perceived to be inadequate such as the storage of practical student data, information about practicum. Therefore, the author builds a website to improve the practical working system with the aim of this application is to increase the efficiency of practicum.In designing the Website Praktikum Program Biology Study Faculty of Mathematics And Natural Sciences uses waterfall method with stage, Requirements Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, Operation and Maintenance. The software used in building this website is Visual Studio Code, MySQL, and XAMPP. This website has been tested with blackbox testing that generates that every feature in the website can run well. Designing the website of praktikum biology study program faculty of mathematics and natural sciences was developed with the aim as the purpose of information media that facilitates information such as practicum schedule data, practicum modules, lists of practicum values and announcements related to practicum, can assist the head of the laboratory in monitoring the implementation of practicum